Rethinking English as Medium of Instruction Policy in Multilingual Classrooms - Khatri, Krishna Kumar; Regmi, Bhim Prasad (Journal of NELTA Gandaki, 2022)
This paper reports the results of a study that unpacked teachers’ experiences and challenges adopting EMI policy in the public schools’ multilingual classrooms. Building on a phenomenological design, we selected two primary level teachers purposively and collected data through in-depth interviews. Drawing upon the thematic analysis and interpretation of the data, the study revealed that teachers perceived EMI as a tool for achieving English language proficiency for the students and a means for the public schools to compete with their private counterparts. Contrarily, EMI in the public school’s multilingual classrooms was found to be practised just as slogan and insufficient for effective students’ participation in classroom learning. Since EMI leads multilingual learners towards monolingual direction, it has posed problems to both the teachers and students due to the low English language proficiency. The study implies that the EMI policy in the lower grades of public schools should be implemented considering the linguistic and cultural milieus of the students.